Childhood abuse and association with adult depressive symptoms among people with cardiovascular disease - Yin, Ruoyun; Yang, Yuan; Tang, Lei; Chang, Yujiao; Zhang, Fan (Frontiers in Public Health, 2023)
Background To study the association between the total/different types of childhood abuse and adult depressive symptoms in people with cardiovascular disease (CVD). Methods The subjects were people with CVD who continuously participated in the China Health and Retirement Longitudinal Study (CHARLS) life history survey and the 2018 wave of the CHARLS national baseline Survey. Multi-level logistic regression models were used to analyze the relationship between emotional neglect, physical neglect, physical abuse and adult depressive symptoms. Results A total of 4,823 respondents were included in this study. The incidence of childhood abuse (existed emotional neglect, physical neglect or physical abuse) was 43.58% among people over 45 years old with CVD, which was higher than that of the general population (36.62%, p < 0.05). Adjusted model showed that overall childhood abuse was associated with adult depressive symptoms (OR = 1.230, 95%CI:1.094–1.383). Among different types of childhood abuse, only physical abuse was associated with depressive symptoms in adulthood (OR = 1.345, 95%CI:1.184–1.528). Conclusion Compared with that of the general population, the incidence of childhood abuse in CVD population is higher. Physical abuse in childhood increased the risk of depressive symptoms in adulthood. It suggested that the occurrence of depressive symptoms was the result of related factors in the whole life course. In order to prevent the depressive symptoms, childhood abuse also needs to be considered. It is very important to identify and prevent the continuation of childhood abuse in time.